Interaction of arch type and footwear on running mechanics - Butler, R. J.; Davis, I. S.; Hamill, J. (The American Journal of Sports Medicine, 2006)
Running shoes are designed to accommodate various arch types to reduce the risk of lower extremity injuries sustained during running. Yet little is known about the biomechanical changes of running in the recommended footwear that may allow for a reduction in injuries.